Treatment options for recurrent primary CNS lymphoma - Kaulen, Leon D.; Bähring, Joachim (Current treatment options in oncology, 2022)
Primary CNS lymphoma (PCNSL) constitutes a rare extranodal variant of non-Hodgkin lymphoma (NHL) with an annual incidence of 0.45/100,000. Given the paucity of large prospective clinical trials, there is no consensus treatment for refractory or relapsed (r/r) PCNSL, and available strategies are largely based on retrospective analyses. Patient age, performance status, previously administered treatment, duration of response, and molecular characteristics guide selection of salvage therapy. Patients with a good performance status (KPS >70), particularly ≤65 years, and adequate organ function should be considered for salvage polychemotherapy. Based on its high overall response rate even in the relapsed setting, we choose high-dose (≥ 3.5g/m2) methotrexate (HD-MTX) based regimens, e.g., R-MPV (rituximab, HD-MTX, procarbazine, and vincristine), for remission re-induction as long as patients were sensitive to first line HD-MTX-based regimens, especially when duration of previous response was ≥ 1 year. Following successful remission induction, we choose myeloablative chemotherapy (e.g., thiotepa, busulfan, cyclophosphamide) and subsequent autologous stem cell transplant in curative intent whenever feasible. Alternatively, conventional chemotherapy regimens (for example, monthly HD-MTX) or low-dose whole-brain radiation therapy (WBRT) are selected for consolidation in non-transplant candidates in complete remission. In cases of HD-MTX refractory disease or contraindications, we use pemetrexed; temozolomide/rituximab; high-dose cytarabine; or whole brain radiation for remission induction. Clinical trial participation is considered as well. Emerging therapies for upfront or salvage therapy under ongoing investigation include bruton tyrosine kinase inhibition (e.g., ibrutinib), immunomodulatory drugs (e.g., lenalidomide), immune checkpoint inhibitors (ICI, e.g., nivolumab), and chimeric antigen receptor T (CAR-T) cell therapy.